A successful management of children with retroperitoneal abscess due to recurrent renal staghorn calculi - Krisni Subandiyah; Astrid Kristina Kardani; Tita Luthfia Sari (Pediatric Sciences Journal, 2024)
Introduction: A particular kind of urolithiasis known as "staghorn calculi" occurs when the calculus grows into the pelvis and renal calyces. It was characterised by fast growth, which might progress to kidney damage and result in other consequences if left untreated. Although the disease's clinical presentation in paediatric patients might be non-specific, it still dramatically raises morbidity and death rates. This case report aimed to identify the risk factors, clinical manifestation, and treatment of children with retroperitoneal abscesses due to recurrent renal calculi. Case description: We describe a case of a young woman with severe acute malnourishment who had a history of painful swelling in her left renal angle after contracting a urinary tract infection. A radiological examination revealed a massive staghorn calculus in the left kidney with significant hydronephrosis, resulting in a retroperitoneal abscess. The patient had surgical treatment along with free drainage of 1000 millilitres of pus. The systemic antibiotic was given as urosepsis treatment. Percutaneous nephrolithotomy (PCNL) and placement of a double-J catheter were performed as definitive treatment for staghorn calculi three months later. Interestingly, it was the second episode of urolithiasis in this patient in 10 years. Malnourishment and recurrent Urinary Tract Infection (UTI) may be predisposing factors to staghorn calculi and perirenal abscess. Conclusion: Considering its significant problem, early evaluation, treatment, and prevention of recurrence were essential to decrease morbidity and mortality in pediatric urolithiasis.